Polycyclic aromatic hydrocarbons and their metabolites in bronchoalveolar lavage and urine samples from patients with inhalation injury throughout their hospitalization: A prospective pilot study - Vyklicka, Katerina; Gregor, Petr; Lipovy, Bretislav; Raska, Filip; Kukucka, Petr; Kohoutek, Jiri; Pribylova, Petra; Čupr, Pavel; Borilova Linhartova, Petra (PloS one, 2024)
BACKGROUND: Specific toxic compounds, such as polycyclic aromatic hydrocarbons (PAHs) and their metabolites, may affect the inhalation injury (INHI) grade, patients' status, and prognosis for recovery. This pilot prospective study aimed to: i) evaluate the suitability of bronchoalveolar lavage (BAL) for determination of PAHs in the LRT and of urine for determination of hydroxylated metabolites (OH-PAHs) in patients with INHI, ii) describe the dynamic changes in the levels of these toxic compounds, and iii) correlate these findings with clinical variables of the patients with INHI. METHODS: The BAL and urine samples from 10 patients with INHI were obtained on Days 1, 3, 5, 7, and 14 of hospitalization, if possible, and PAHs (BAL) and OH-PAHs (urine) were analyzed using chromatographic methods (GC-MS and HPLC). RESULTS: Concentrations of analyzed PAHs were in most cases and time points below the limit of quantification in BAL samples. Nine OH-PAHs were detected in the urine samples; however, their concentrations sharply decreased within the first three days of the hospitalization. On Day 14, the total amount of OH-PAHs in urine was higher in surviving patients with High-grade INHI (≥3) than in those with Low-grade INHI (<3, p = 0.032). Finally, a significant correlation between certain OH-PAHs and clinical variables (AST/ALT, TBSA, ABSI) from Day 1 of the hospitalization was observed (p<0.05). CONCLUSIONS: BAL samples are not suitable for the analysis of PAHs. However, the OH-PAHs levels in urine can be measured reliably and were correlated with several clinical variables. Moreover, High-grade INHI was associated with higher total concentrations of OH-PAHs in urine.
Keywords: Male; lidé středního věku; Prospective Studies; Pilot Projects; Humans; Middle Aged; senioři; pilotní projekty; hospitalizace; prospektivní studie; mužské pohlaví; polycyklické aromatické uhlovodíky; Female; Aged; ženské pohlaví; Adult; Polycyclic Aromatic Hydrocarbons; bronchoalveolární lavážní tekutina; Hospitalization; Bronchoalveolar Lavage Fluid; lidé; dospělí